China : - Chai, Joseph C.H. (Clarendon Press, 1997)
At the heart of China's remarkable economic growth is a new economic system, which has emerged out of radical reforms in virtually all areas of economic activity. Understanding this system is the key to understanding the Chinese economy. This book, the culmination of many years of research in Hong Kong and China, is a comprehensive account of these systemic reforms, as well as of their transferability to other economies in transition.